Traslados de pacientes desde servicios de urgencias a otras áreas del hospital: análisis de modos de fallo y efectos. - Prieto-Molina, Antonio; Aranda-Gallardo, Marta; Moya Suarez, Ana Belen; Rivas-Ruiz, Francisco; Peláez-Cherino, Joaquín; Canca-Sánchez, José Carlos; Prieto-Molina, Antonio (Sociedad Española de Medicina de Urgencias y Emergencias, 2023)
Objectives: To perform an in-depth analysis of the process of transferring patients from an emergency department (ED) to other areas inside a hospital and identify possible points of failure and risk so that strategies for improvement can be developed. Material and methods: We formed a multidisciplinary group of ED and other personnel working with hospitalized adults. The group applied failure mode and effects analysis (FMEA) to understand the in-hospital transfer processes. A risk priority scoring system was then established to assess the seriousness of each risk and the likelihood it would appear and be detected. Results: We identified 8 transfer subprocesses and 14 critical points at which failures could occur. Processes related to administering medications and identifying patients were the components that received the highest risk priority scores. Improvement strategies were established for all risks. The group created a specific protocol for in-hospital transfers and a checklist to use during handovers. Conclusión: The FMEA method helped the group to identify points when there is risk of failure during patient transfers and to define ways to improve patient safety.
Patient transfers from emergency departments to other in-hospital areas: a failure mode and effects analysis
Autorización en correo RIUMA (09/01/25)
Keywords: Enfermos - Movilización; Servicios de salud - Gestión del riesgo; Análisis Modal de Fallos y Efectos (AMFE); Clinical safety; Gestión de riesgos; Patient transport; Risk management; Seguridad clínica; Transferencia de pacientes; Failure mode and effects análisis (FMEA)